BVS Homeopatía Brasil: una revisión histórica sobre su papel en la visibilidad y acceso al conocimiento homeopático. - Ragacini, Leonardo Adriano; Chávez-Martínez, Omar (Revista Medica del IMSS)
The Virtual Health Library on Homeopathy (BVS Homeopatia Brasil) represents a pioneering initiative in the organization, digitization, and dissemination of homeopathic knowledge in Latin America. This article presents a narrative review of its trajectory, from the informational invisibility of homeopathy during the 1970s and 1980s to its consolidation as the main specialized digital repository in the field. Key milestones are analyzed: the creation of the HOMEOINDEX database, the development of the HP category in the DeCS thesaurus, the leadership of Dr. Matheus Marim in the digital transition, and the institutionalization of the BVS through agreements with BIREME, Pan American Health Organization (PAHO), World Health Organization (WHO), and the Brazilian Ministry of Health. The article also describes its current features, recent technological updates, and the incorporation of artificial intelligence as an emerging challenge. The review identifies BVS Homeopatia as a successful model for democratizing access to scientific knowledge, sustained by interinstitutional cooperation and active community engagement. It concludes that its sustainability will depend on continued use by professionals and the general public, as well as on its capacity to adapt to the technological and epistemological transformations of the 21st century.